Entrepreneurship, information, and economic growth - Bunten, Devin, author; Weiler, Stephan, advisor; Phillips, Ronnie J., 1951-, committee member; Zahran, Sammy J., committee member (Colorado State University. Libraries, 2010)
This thesis analyzes the impact of entrepreneurship on economic growth across US cities within a formal production function approach. Like previous analyses of economic growth--but unlike many studies of entrepreneurship--economic growth is measured in personal income per worker. The production function features three traditional inputs with a novel fourth: entrepreneurial capital. Entrepreneurship is a process of information revelation which produces a dynamic externality providing marketplace information to potential future market entrants, outside firms, lenders and others. Entrepreneurial capital measures the contribution of this information to economic growth. Multiple measurements of entrepreneurial capital are used, each emphasizing different aspects of the entrepreneurial environment. The statistical results support the views that entrepreneurship is a causal input to local economic growth, that the effects of entrepreneurship are geographically localized, and that the thicker markets of large cities.
Keywords: economic growth; entrepreneurship; Entrepreneurship; Economic development; Capital